Adhesion of Resin-Resin and Resin–Lithium Disilicate Ceramic: A Methodological Assessment - Guggenbühl, Simon (Materials (Basel), 2021)
The aim of this study was to evaluate four test methods on the adhesion of resin composite to resin composite, and resin composite to glass ceramic. Resin composite specimens (N = 180, Quadrant Universal LC) were obtained and distributed randomly to test the adhesion of resin composite material and to ceramic materials (IPS e.max CAD) using one of the four following tests: (a) Macroshear SBT: (n = 30), (b) macrotensile TBT: (n = 30), (c) microshear µSBT: (n = 30) and (d) microtensile µTBT test (n = 6, composite-composite:216 sticks, ceramic-composite:216 sticks). Bonded specimens were stored for 24 h at 23 °C. Bond strength values were measured using a universal testing machine (1 mm/min), and failure types were analysed after debonding. Data were analysed using Univariate and Tukey’s, Bonneferroni post hoc test (α = 0.05). Two-parameter Weibull modulus, scale (m), and shape ((0)) were calculated. Test method and substrate type significantly affected the bond strength results, as well as their interaction term (p < 0.05). Resin composite to resin composite adhesion using SBT (24.4 ± 5)(a), TBT (16.1 ± 4.4)(b) and µSBT (20.6 ± 7.4)(a,b) test methods presented significantly lower mean bond values (MPa), compared to µTBT (36.7 ± 8.9)(b) (p < 0.05). When testing adhesion of glass ceramics to resin composite, µSBT (6.6 ± 1)(B) showed the lowest and µTBT (24.8 ± 7)(C,D) the highest test values (MPa) (SBT (14.6 ± 5)(A,D) and TBT (19.9 ± 5)(A,B)) (p < 0.05). Resin composite adhesion to ceramic vs. resin composite did show significant difference for the test methods SBT and µTBT (resin composite (24.4 ± 5; 36.7 ± 9 MPa) vs. glass ceramic (14.6 ± 5; 25 ± 7 MPa)) (p > 0.05). Among substrate–test combinations, Weibull distribution presented the highest shape values for ceramic–resin in µSBT (7.6) and resin–resin in µSBT (5.7). Cohesive failures in resin–resin bond were most frequently observed in SBT (87%), followed by TBT (50%) and µSBT (50%), while mixed failures occurred mostly in ceramic–resin bonds in the SBT (100%), TBT (90%), and µSBT (90%) test types. According to Weibull modulus, failure types, and bond strength, µTBT tests might be more reliable for testing resin-based composites adhesion to resin, while µSBT might be more suitable for adhesion testing of resin-based composites to ceramic materials.